2020
DOI: 10.3390/ph13100314
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Targeted Delivery of Pre-miR-29b Using Lactoferrin-Stearic Acid-Modified-Chitosan/Polyethyleneimine Polyplexes

Abstract: The efficacy of brain therapeutics is largely hampered by the presence of the blood–brain barrier (BBB), mainly due to the failure of most (bio) pharmaceuticals to cross it. Accordingly, this study aims to develop nanocarriers for targeted delivery of recombinant precursor microRNA (pre-miR-29b), foreseeing a decrease in the expression of the BACE1 protein, with potential implications in Alzheimer’s disease (AD) treatment. Stearic acid (SA) and lactoferrin (Lf) were successfully exploited as brain-targeting li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Finally, the peptide-SA conjugate was redispersed in dH2O and lyophilized. The molecular weight of the lyophilized conjugate was determined by LC-ESI-MS (31,32).…”
Section: Conjugation Of the Peptide With Stearic Acidmentioning
confidence: 99%
“…Finally, the peptide-SA conjugate was redispersed in dH2O and lyophilized. The molecular weight of the lyophilized conjugate was determined by LC-ESI-MS (31,32).…”
Section: Conjugation Of the Peptide With Stearic Acidmentioning
confidence: 99%
“…A widely used method is the packaging in polyplexes, consisting of polymers and complexed nucleic acids, which has been exploited in various studies [ 273 , 274 , 275 , 276 ]. Here, the toxicity needs to be balanced with the miR binding capacity.…”
Section: Delivery Of Mir Therapeuticsmentioning
confidence: 99%
“…Amino acid-based molecules were also studied to in relation to BBB transport and to delivery of anticancer agents [45,46]. Furthermore, poly-amine materials such as polyamidoamine (PAMAM) dendrimers were also reported as a platform for brain drug delivery [47][48][49]. Fana et al reported that PAMAM nanocarriers can be used to deliver bioactive molecules for the treatment of glioblastoma [48].…”
Section: Discussionmentioning
confidence: 99%
“…Fana et al reported that PAMAM nanocarriers can be used to deliver bioactive molecules for the treatment of glioblastoma [48]. Pereira et al reported that recombinant-precursor microRNA (pre-miR-29b) was delivered to the brain with the aid of nanocarriers based on chitosan/polyethyleneimine (PEI) [49]. They argued that chitosan-based nanocarriers can deliver pre-miR-29b across the BBB more efficiently than PEI-based carriers.…”
Section: Discussionmentioning
confidence: 99%